Exploring banking business model types: A cognitive view - Payam Hanafizadeh; Seyedali Marjaie (Digital Business, 2021)
The value creation mechanism in a business model is based on a thoughtful configuration of mostly intangible microfoundations. The business model concept is rooted in business logic and strategic management literature. Banking literature lacks the business model concept, which is described based on subjective ideas and qualitative approaches. This article aims to explain the business model concept in banking with a cognitive view. For this purpose, we have qualitatively studied 50 cases of business models of innovative and leading banks and their value proposition structure. Through content analysis, four types of banking business models emerged. The findings proposed a banking business model presented at three levels, i) generic banking business model, ii) types of banking business models, and iii) instances of implementations at the realization level. The constructing microfoundations of each type and their composition are discussed in detail. Actual cases (instances) implemented in the industry are also presented and discussed as evidence of the realization of type models.
Keywords: 650; Business model; Banking industry; Business model types